Pemberdayaan Perempuan Pedesaan dengan Pendekatan Participatory Action Research: Produksi Sabun Cuci Piring Herbal Rumahan - Suryaneta Suryaneta; Kiki Yuli Handayani; Amelia Sri Rezki; Achmad Gus Fahmi; Iwan Syahjoko Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This article aimed to do research on the economic empowerment of rural women using Participatory Action Research approach. PAR required performing research to define a problem or implement information as solutions to problems that have been defined. PAR is